MEMBENTUK KARAKTER KRISTIANI YANG TANGGUH DI ERA SOCIETY 5.0 : PERAN PENDIDIKAN AGAMA KRISTEN - Katili, Funixman; Suhendra (JURNAL IMPARTA, 2025)
This study examines the role of religious education in shaping resilient Christian character in the era of Society 5.0, where rapid technological and informational developments present complex challenges. Religious education plays a crucial role in building mental and social resilience while providing a strong moral foundation for the younger generation. Data from the Central Bureau of Statistics (BPS) show that 70% of Indonesian adolescents experience mental pressure due to the rapid technological advancements, highlighting the importance of holistic education. Findings from Satya Wacana Christian University reveal that students actively involved in religious education demonstrate more positive social behavior. Additionally, the use of technology in religious education increased by 40% during the COVID-19 pandemic, offering opportunities for innovative learning. However, only 30% of religious education teachers have received specialized training, indicating the need for educational reforms to enhance teaching quality. This study underscores that effective religious education can shape Christian character capable of facing the challenges of the Society 5.0 era.